M1 muscarinic receptor activation decreases alcohol consumption via a reduction in consummatory behavior - Leigh C. Walker; Erin J. Campbell; Kate L. Huckstep; Nicola A. Chen; Christopher J. Langmead; Andrew J. Lawrence (Wiley, 2022)
Abstract Muscarinic acetylcholine receptors (mAChRs) have been shown to mediate alcohol consumption and seeking. Both M4 and M5 mAChRs have been highlighted as potential novel treatment targets for alcohol use disorders (AUD). Similarly, M1 mAChRs are expressed throughout reward circuitry, and their signaling has been implicated in cocaine consumption. However, whether the same effects are seen for alcohol consumption, or whether natural reward intake is inadvertently impacted is still unknown. To determine the role of M1 mAChRs in alcohol consumption, we tested operant self‐administration of alcohol under both fixed ratio (FR3) and progressive ratio (PR3‐4) schedules. Enhancing M1 mAChR signaling (via the M1 PAM‐Agonist PF‐06767832, 1 mg/kg, i.p.) reduced operant alcohol consumption on a fixed schedule but had no effect on motivation to acquire alcohol. To determine whether these actions were specific to alcohol, we examined the effects of M1 enhancement on natural reward (sucrose) self‐administration. Systemic administration of PF‐06767832 (1 mg/kg, i.p.) also reduced operant sucrose self‐administration, suggesting the actions of the M1 receptor may be non‐selective across drug and natural rewards. Finally, to understand whether this reduction extended to natural consummatory behaviors, we assessed home cage standard chow and water consumption. M1 enhancement via systemic PF‐06767832 administration reduced food and water consumption. Together our results suggest the M1 PAM‐agonist, PF‐06767832, non‐specifically reduces consummatory behaviors that are not associated with motivational strength for the reward. These data highlight the need to further characterize M1 agonists, PAMs, and PAM‐agonists, which may have varying degrees of utility in the treatment of neuropsychiatric disorders including AUD.